Urine angiostatin and VCAM‐1 surpass conventional metrics in predicting elevated renal pathology activity indices in lupus nephritis. (26th October 2017) - Soliman, Samar; Mohamed, Fatma A.; Ismail, Faten M.; Stanley, Samantha; Saxena, Ramesh; Mohan, Chandra
Abstract: Aim: The goal of this study is to investigate how urinary angiostatin, vascular cell adhesion molecule 1 (VCAM‐1) and established measures of renal function relate to specific histologic findings in paired kidney biopsy samples from patients with lupus nephritis (LN). Method: Urine samples were collected from 54 LN patients together with paired kidney biopsy samples and examined for urinary angiostatin and VCAM‐1 protein levels. Nonparametric tests were used to examine the association of both urinary biomarkers and established traditional laboratory markers of renal function with nine specific renal histologic features seen in LN, including glomerular leukocyte infiltration, endocapillary proliferation, cellular crescents, fibrinoid necrosis, wire loops, interstitial inflammation, glomerulosclerosis, fibrous crescents, tubular atrophy and interstitial fibrosis. Results: Compared to traditional renal disease metrics, both urinary angiostatin and VCAM‐1 exhibited outstanding potential (area under the curve 0.97, 0.98, respectively) to predict renal biopsy activity index score ≥ 7, which is associated with poor long‐term prognosis. Whereas urine VCAM‐1 was most significantly associated with fibrous crescents, urine angiostatin was most significantly associated with endocapillary proliferation, cellular crescents, fibrinoid necrosis and fibrous crescents in concurrent renal biopsies. Conclusion: Urinary angiostatin and VCAM‐1 are predictive of specific histological changes in concurrent LN renal biopsies. Both urinary biomarkers are good candidates for use as noninvasive measures of renal pathology activity changes in LN.